Correlations of disease severity and age with hematology parameter variations in patients with COVID‐19 pre‐ and post‐treatment. Issue 1 (21st November 2020) - Liang, Juanying; Nong, Shaoyun; Jiang, Liejun; Chi, Xiaowei; Bi, Dewu; Cao, Jun; Mo, Lida; Luo, Xiaolu; Huang, Huayi
Abstract: Background: For better understanding of the pathological changes of COVID‐19, benefiting clinical management of the disease and the preparation for future waves of similar pandemics. Methods: Hematology parameters from a total of 52 cases of COVID‐19 admitted for treatment in a designated hospital were retrospectively analyzed. Data were analyzed by SPSS statistical software. Results: Pre‐treatment T‐cell subsets, total lymphocytes, red blood cell distribution width (RDW), eosinophils, and basophils were significantly lower than that of post‐treatment, while the inflammatory indexes neutrophils, neutrophil to lymphocyte ratio (NLR), and C‐reactive protein (CRP) levels, as well as red blood cell (RBC) and hemoglobin, were significantly reduced after treatment. The T‐cell subsets, total lymphocytes, and basophils in severely and critically ill patients were significantly lower than those in moderately ill patients. Neutrophils, NLR, eosinophils, procalcitonin (PCT), and CRP was significantly higher in severely and critically ill patients than in moderately ill patients. CD3+, CD8+, total lymphocytes, platelets, and basophils in patients older than 50 were lower than that of those younger than 50, while neutrophils, NLR, CRP, and RDW in patients older than 50 were higher than that of younger than 50. There was a positive correlation among prothrombin time (PT), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) in severely and critically ill patients. Conclusions: T‐cell subsets, lymphocyte count, RDW, neutrophils, eosinophils, NLR, CRP, PT, ALT, and AST are important indicators in the management especially for severely and critically ill patients with COVID‐19. Abstract : This work was to observe the correlation of the inflammatory indexes in the blood of COVID‐19 patients pre‐ and post‐ treatment for better understanding of the pathological changes of COVID‐19 benefiting clinical management of the disease and the preparation for future waves of similar pandemics.